2019
DOI: 10.1093/aesa/say050
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops Enhance Natural Enemies While Help Suppressing Pests in a Tea Plantation

Abstract: Tea is an economically important crop, consumed by billions of people. Despite the increasing market for pesticide-free products, the use of pesticide in tea is still high. In order to investigate whether intercropping promotes biological control organisms, Chamaecrista rotundifolia (Pers.) Greene, Indigofera hendecaphylla Jacq., Trifolium repens L., and Vigna sinensis (L.) were separately intercropped with free weeding as control in a tea plantation at Yangli, China. Arthropods were collected by taking sweep-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…Nevertheless, weeded, bare ground rows (Bar) also showed significantly higher species richness than in the control. The underlying mechanisms of the two significant differences, however, are probably different; C. rotundifolia likely attracts beneficial insects by providing shelter or other resources (Chen et al , 2019a, b), whereas bare soil surfaces open up opportunities for ambush predators to easily find prey (Schmidt & Rypstra, 2010). Since these normally generalist species that are specifically adapted to disturbed habitats are more likely to stay in the adjacent field margins, their long-term value in tea canopies as biological control agents may be limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, weeded, bare ground rows (Bar) also showed significantly higher species richness than in the control. The underlying mechanisms of the two significant differences, however, are probably different; C. rotundifolia likely attracts beneficial insects by providing shelter or other resources (Chen et al , 2019a, b), whereas bare soil surfaces open up opportunities for ambush predators to easily find prey (Schmidt & Rypstra, 2010). Since these normally generalist species that are specifically adapted to disturbed habitats are more likely to stay in the adjacent field margins, their long-term value in tea canopies as biological control agents may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence on efficacy of cover crops in enhancing beneficial species in tea plantations is mixed (Chen et al , 2019a, b). Song et al (2006) found that predatory Coleoptera abundance was significantly higher in tea interplanted with white clover ( Trifolium repens L., 1753) compared to tea monocultures, and this change led to better suppression of hemipteran pests.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study site, carabids were not a dominant group (G. Pozsgai, FAFU, Fuzhou, personal communication), and they are mostly night-active [38]; thus, one would not expect such a reciprocal relationship if carabids were responsible for most of the attacks on our caterpillars. It is plausible to assume that most of the arthropod attacks were made by day-active predators, such as ants and spiders, that are common in these habitats [11], and these would be directly threatened by invertivorous birds looking for food. It was also clear that at least some bird species were more active on the tea plantation than in the forest fragment (T. Imboma, personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…Several major pests of tea are arthropods [10]; therefore, biocontrol agents in tea ecosystems could be important. Planting various flowering plants in-between rows of tea in Fujian can increase the abundance of various natural enemies [11], and increase their potential to control pests in tea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation